Analysis of network behavior characteristic and influence factor based on the peak traffic - Ai-ping ZHOU; Guang CHENG (Tongxin xuebao)
Based on the burstiness of network traffic,the peak traffic metric was introduced,and the method which was used to evaluate network operation and plan capacity was proposed.The network intrinsic features and the peak traffic for the 21 CERNET campus networks were analyzed by statistical methodologies(analysis of variance and analysis of covariance),so that the peak traffic is mutually independent and follows Gaussian distribution,the network intrinsic features have dominant impact on the peak traffic,and the number of network users is highly related to link bandwidth demand.On the basis,the linear regression model and capacity planning model were constructed.Experimental results illustrate that the proposed capacity planning model is used to evaluate the access bandwidth of new campus networks exactly.